Prevalence of Disc Degeneration in Asymptomatic Korean Subjects. Part 1 : Lumbar Spine - Kim, Sang Jin (The Korean Neurosurgical Society, 2013)
OBJECTIVE: Asymptomatic patients show high degeneration prevalence at lumbar disc in previous literatures. Unfortunately, there are few Korean data, so the authors attempted to analyze the prevalence of disc degeneration in highly selective asymptomatic Korean subjects using MRI. METHODS: We performed 3 T MRI sagittal scans from T12 to S1 on 102 asymptomatic subjects (50 men and 52 women) who visited our hospital between the ages of 14 and 82 years (mean age 46.3 years). All images were read independently by three observers (two neurosurgeons and one neuroradiologist) who were not given any information about the subjects. We classified grading for lumbar disc herniation (HN), annular fissure (AF), and nucleus degeneration (ND), using disc degeneration classification. RESULTS: The prevalence of HN, AF, and ND were 81.4%, 76.1%, and 75.8% respectively. Almost all levels showed an age-related proportional tendency with some exceptions. CONCLUSION: In asymptomatic Korean subjects, the abnormal findings showed high prevalence of AF, ND, and extrusion. Especially in young ages, the authors found that bulging, protrusion, and AF showed high prevalence at L4/5 and L5/S1. And ND showed high prevalence at L5/S1. So, all lumbar disc degenerations are not pathologic, especially in children and adolescents.